2002
DOI: 10.1103/physrevlett.89.149704
|View full text |Cite
|
Sign up to set email alerts
|

Kötzleret al. Reply:

Abstract: Kötzler et al. Reply: The Comment [1] picks up two features of our Letter [2] and proposes alternative interpretations of both in terms of results for the 2D XY model [3]. In this Reply, we argue that our key conclusion, i.e., the loss of superconducting (SC) phase coherence via a thickness-induced vortex-loop (VL) unbinding at T ? d below the virtual 3D bulk transition T c [see Fig. 1(a)], is not weakened by the given reasons. The other point of the Comment addresses the onset of SC phase fluctuations observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
148
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 4 publications
(2 reference statements)
7
148
0
Order By: Relevance
“…Such discrepancy was commonly observed in measurements of ac magnetic responses of ultrathin SC films. 3,30,31 It is generally understood to be a 2D effect due to diffusive motion of thermally excited vortex−antivortex. 3,6 Presumably because of reduced pinning or viscosity, the vortex−antivortex excitations are more diffusive for thinner SC films.…”
mentioning
confidence: 99%
“…Such discrepancy was commonly observed in measurements of ac magnetic responses of ultrathin SC films. 3,30,31 It is generally understood to be a 2D effect due to diffusive motion of thermally excited vortex−antivortex. 3,6 Presumably because of reduced pinning or viscosity, the vortex−antivortex excitations are more diffusive for thinner SC films.…”
mentioning
confidence: 99%
“…Table 1 presents the range of impact parameter b, the mean numbers of NTotal , NPart and NSpec in different centrality Au+Au collisions at √ s NN = 200 GeV. In calculations we take σ in NN =42 mb [21] , and the centrality bins are defined as the percentages of the total inelastic cross section σ in AuAu =6.9 b. The values inside the parentheses are the results given by the BRAHMS Collaboration [9] .…”
Section: The Number Of Participants and Spectatorsmentioning
confidence: 99%
“…[1−3,10−13] In general, the three-dimensional (3D) axially symmetric harmonic trap has extreme symmetry, thus the BEC has either a cigar or a disk shape. [14] In the practical situation of experiments, the trap is usually not purely harmonic. At the same time, motivated by a recent experiment, [15] the effect of DDIs on the collective excitation frequency was considered and it was shown that the collective mode is very sensitive to the trap geometry.…”
mentioning
confidence: 99%